PHONATION AND SPEECH RECOVERY IN CANCER PATIENTS WITH MAXILLARY DEFECTS - A. A. Kulakov; V. M. Chuchkov; E. G. Matyakin; I. S. Romanov; A. A. Akhundov; A. M. Mudunov; S. P. Fedotenko; N. N. Fedotov; S. O. Podvyaznikov; M. A. Kropotov; O. A. Zharkov; A. V. Chizhova; et al. (Опухоли головы и шеи)
Speech quality was evaluated in 188 patients with acquired maxillary defects. Prosthetic treatment of 29 patients was preceded by pharmacopsychotherapy. 63 patients had lessons with a logopedist and 66 practiced self-tuition based on the specially developed test. 30 patients were examined for the quality of speech without preliminary preparation. Speech quality was assessed by auditory and spectral analysis. The main forms of impaired speech quality in the patients with maxillary defects were marked rhinophonia and impaired articulation. The proposed analytical tests were based on a combination of “difficult” vowels and consonants. The use of a removable prostheses with an obturator failed to correct the affected speech function but created prerequisites for the formation of the correct speech stereotype. Results of the study suggest the relationship between the quality of speech in subjects with maxillary defects and their intellectual faculties as well as the desire to overcome this drawback. The proposed tests are designed to activate the neuromuscular apparatus responsible for the generation of the speech. Lessons with a speech therapist give a powerful emotional incentive to the patients and promote their efforts toward restoration of speaking ability. Pharmacopsychotherapy and self-control are another efficacious tools for the improvement of speech quality in patients with maxillary defects.